IMPLEMENTATION OF E- LEARNING ON THE TEACHING ENGLISH AS GLOBAL LANGUAGE IN THE PANDEMIC-ERA - Umar Umar (Jurnal Inovasi Penelitian, 2021)
This study aims to determine the effectiveness of the implementation e-learning during pandemic era Covid-19. The method used is a descriptive qualitative method. The participants in this study amounted to 11 students of 3rd semester of STKIP Paracendekia NW Sumbawa. Data collection techniques in this study used questionnaires with Likert scale and interview. Data analysis techniques used Likert Scale Assessment. The results showed that learning with implementation e-learning applications were effective, interactive, could support distance learning, making it easier for students to absorb the learning material delivered by lecturer during Pandemic Covid-19.